Has Methodism’s ‘White History’ Determined Its ‘Black Future’? African Traditional Healing and the Methodist Church of Southern Africa - David Elliott (Religions)
Postcolonial discourses on religion have extensively explored the intersections of race and religion. Particular research within such discourses has been conducted to explore the intersection of Whiteness and Christianity in postcolonial contexts. The Methodist Church of Southern Africa (MCSA) is an example of a postcolonial Christian denomination that seeks to assert itself as ‘authentically African’ whilst having a distinctly colonial, missionary history in Southern Africa. This article explores the enduring intersections of Whiteness and Christianity in the MCSA through analyzing the methodology and theoretical framework of a discussion document produced by the MCSA to explore the relationship between Methodism, ukuthwasa, and African Indigenous Religion. I contend that the MCSA structurally and epistemically, albeit unintentionally, reproduces Whiteness through privileging seemingly universal Methodist methods, theories, and concepts for producing theological knowledge that are colonially produced and continue to underscore the infrastructure of MCSA ecclesiology. The stubborn persistence of colonially inherited epistemologies is particularly evident when we see how a potentially groundbreaking document on ukuthwasa (calling) is subjected to the constraints of the very epistemic traditions it is intended to dislodge. Furthermore, I argue that, through the persistence of this epistemology, the MCSA moves to domesticate and civilize the African Indigenous in Southern Africa.